Phosphorus fertilization in sugarcane cultivation under different soil managements - Paulo R. de Sousa Junior; Caio A. C. G. Brunharo; Carlos E. A. Furlani; Renato de M. Prado; Walter Maldonado Júnior; Cristiano Zerbato (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Soil preparation along with its chemical adjustment is the most important step in sugarcane plantation, especially because it provides proper conditions for plant development. The objective of the present research was to evaluate sugarcane response to the application of different phosphorus doses and their location, associated with both minimum soil tillage and conventional soil tillage. The experiment was conducted in a split-split-plot randomized block design, where the main plots were subjected to soil managements (minimum soil tillage or conventional soil tillage), the subplots to phosphorus doses in total area, and the sub-sub-plots to phosphorus doses in the crop rows. The evaluated variables were soil chemical parameters, sugarcane production and sugar production. Minimum tillage led to larger phosphorus accumulation and higher percentage of exchangeable bases in the soil, whereas the highest P dose in total area in the crop rows led to reduction of sugar production.